The Internet, Social Media, and a Changing China - deLisle, Jacques, 1961-; Goldstein, Avery, 1954-; Yang, Guobin (Book collections on Project MUSE., 2016)
The Internet and social media are pervasive and transformative forces in contemporary China. The Internet, Social Media, and a Changing China explores the changing relationship between China's Internet and social media and its society, politics, legal system, and foreign relations.